TRENDS IN MATERNAL EMPLOYMENT AND EDUCATION STATUS OF STUNTING AND NON-STUNTING TODDLERS IN COASTAL AREAS OF KENDARI CITY: STUNTING - Fatmawati, Fatmawati; Petrus; Kristianto, Jusuf; Abadi, Ellyani; Ayu Dwi Putri, Tenri Zulfa (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Stunting is a major nutritional problem in Indonesia that can determine the quality of resources. Stunting children are susceptible to disease, have difficulty in physical and cognitive development, and are at risk of developing degenerative diseases as adults. The prevalence of stunting in 2021 was 0.95%, 2022 was 1.4% and 2023 was 1.69%. The aim of this study was to determine the trend of maternal employment and education in stunted and non-stunted toddlers. Methods: This type of research is descriptive research with a cross-sectional study design. The population of the study was all toddlers in the coastal area of Kendari City. The sample was part of toddlers in the coastal area of Kendari City in 2024, consisting of 35 intervention groups and 35 control groups. Data were collected using questionnaires and descriptive data analysis. Results: Mothers' jobs were not working, namely as housewives, as many as 85.7% in the intervention group and 80% in the control group were housewives. Most of the mother’s education in the intervention and control groups, most of them were high school graduates, namely 45.6% in the intervention group and 54.1% in the control group. Conclusion: The mothers' occupations in stunted and non-stunted toddlers are mostly housewives and the mothers' education are mostly high school graduates.